A balancing cam mechanism for minimizing the torque fluctuation of engine camshafts. (February 2017) - Lin, Deng-Ying; Hou, Bo-Jiun; Lan, Chao-Chieh
Abstract: This paper presents the design and experiment of a balancing cam mechanism to minimize the torque fluctuation of engine camshafts. Torque fluctuation of rotary machines causes unwanted vibration that would impair their performance and reliability. The combination of inertia, driving, and resistive torque fluctuations on engine crankshafts and camshafts is the major source of vehicle vibration. For camshafts, the magnitude of resistive torque fluctuation is more substantial than that of inertia torque fluctuation at low to medium speeds. While previous methods focused on suppressing or isolating vibration motion from engine to chassis, the proposed method seeks to directly reduce the torque fluctuation on engine shafts. The balancing mechanism consists of a cam, rocker, and spring. Given a resistive torque curve of a camshaft, the cam profile can be synthesized such that the output balancing torque cancels with the original resistive camshaft torque. Thus the camshaft will statically generate zero output torque. Based on a derived camshaft torque model, a design process of the cam profile is presented. The effect of inertia torque at various speeds is compared with the balancing torque. Finally, a prototype and its associated experiments are presented to demonstrate the torque balancing performance. Highlights: A balancing cam is presented to remove the torque fluctuation of engine camshafts. The output balancing torque cancels with the original resistive camshaft torque. The camshaft will statically generate zero output torque. The effect of inertia torque is compared with the balancing torque. A prototype and its associated experiments are presented for demonstration.